Oblicz:
a) (2√8+1/6√18-4√2)×√2=
b) (∛25-∛200)×∛5=
c) √3×(√27+√12)=
d) (3√27-2√12-4√75):√3=
e) (2∛128-2∛54+4∛16):∛2=
f) (4√0,54-5√0,06+7√0,0024+2√0,24):√6=
g) (2∛0,024-4∛0,003+3∛0,081):∛3=

1

Odpowiedzi

2009-10-18T11:25:23+02:00
Masz tu niektóre ;)

a) (2√8+1/6√18-4√2)×√2 = (2√4x√2+1/6√9x√2-4√2)x√2 = (2x2√2 + 1/6x3√2-4√2)x√2 = (4√2+1/2√2-4√2)x√2 = 1/2√2x√2 = 1/2x2 = 1

c) √3×(√27+√12)= √3x(√9x√3+√3x√4) = √3x(3√3+2√3) = √3x5√3 = 5x3 = 15

d) (3√27-2√12-4√75):√3= (3√9x√3-2√3x√4-4√25x√3):√3=
(3x3√3-2x2√3-4x5√3):√3= -15√3:√3 = -15